Impact of High Fidelity Simulation Training on the Quality of Cardiopulmonary Resuscitation Performance among Emergency Medical Services (EMS) Professionals in Pune, India - Anand Hinduja1 , Parag Rishipathak2 , Shrimathy Vijayaraghavan3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: The provision of high quality cardio pulmonary resuscitation (CPR) is a key modifiablefactor associated with survival in cardiac arrest. Management of a patient with cardiac arrest is a dynamicand high-pressure challenge requiring critical decision making in a short period of time. Numerous studiesemphasize that quality of chest compressions directly influences survival rate from cardiac arrest. Hence,improving CPR quality is of paramount importance. This can be achieved by accurate measurement ofvarious CPR metrics and provision of real time feedback to the rescuer.Objective: The study aims to assess impact of high fidelity simulation training on quality of CPR performanceof EMS Professionals.Methods: A high fidelity manikin was utilized to create four unique healthcare simulation scenarios based oncardiac arrest. The manikin software was capable of capturing real-time CPR data and measured parameterslike chest compression depth (CCD), chest compression rate (CCR), chest recoil (CR) and chest compressionfraction (CCF). The participants were initially taught the assessment and management of cardiac arrest. Theparticipants underwent a pre-intervention test conducted on high fidelity manikin. The CPR metrics wererecorded during the session. The participants were then imparted training with real time CPR feedback for aperiod of two months. This was followed by a post-intervention test and the CPR metrics of both tests werecompared.Discussion: The participants showed improvement in chest compression depth and chest compression ratebut the chest recoil frequency and chest compression fraction decreased after the two-month interventionperiod. The overemphasis on achieving target depth and rate led to ignorance of the other two parametersaffecting overall quality of CPR.Conclusion: Maintaining adequate attention on all aspects of CPR metrics is a complex challenge even fortrained professionals. Utilizing technology for real-time feedback is a reliable method to gauge improvementin quality of CPR during training sessions of EMS professionals.